Implementing risk-based inspection approach: Is it beneficial for pressure equipment in Malaysia industries? - Mohamed, Ramuna; Hassan, Che Rosmani Che; Hamid, Mahar Diana (Wiley, 2017)
The transition from time-based inspection to risk–based inspection (RBI) in Malaysian industry began in June 2014 with the gazette of Factories and Machinery (Special Scheme of Inspection) (Risk-Based Inspection) Regulations 2014 (SSI 2014). Under the new regulations, owners shall express their commitment and provide proof of their ability to ensure safety, integrity, and operability of relevant equipment. The regulation does not prescriptively mention methods to implement the RBI approach, but does spell out minimum requirements. Upon successful demonstration of compliance to the authority, the Certificate of Fitness of pressurized equipment may be extended to maximum 72 months. This paper aims to establish the benefits which may accrue from the adoption of RBI approach and ascertain the potential difficulties associated with the implementation of this approach. The paper first presents a review of the literature, establishing the major reasons for, and the benefits of, RBI implementation. This is followed by the results of a Malaysian survey on the implementation of RBM approach. An audit was conducted in the Malaysian petrochemical and chemical industries in April 2016. The audit results highlight the reasons for and benefits of implementing RBI. The paper concludes with a discussion and recommendations for the implementation of the RBI approach.